Avaliação do desempenho de um sistema de refrigeração automotivo com ejetor em ciclo COS - Ferreira, Henrique Schardosin (Universidade do Vale do Rio dos Sinos, 2017)
In this work was presented a study of the use of the ejector in a cooling system for automotive air conditioning, to recover energy losses during the expansion process. A numerical model was used to predict the energetic gain with ejector application based on the ejector standard cycle proposed by Gay (1931). Subsequently, a numerical model was proposed to determine the basic dimensions necessary for the ejector manufacturing. A simulation system for the standard refrigeration cycle for automotive air conditioning was modified for the ejector installation and started to operate according to the COS cycle by Oshitani et al. (2005). From the several mathematical models in the literature, a model of the ejector cycle simulation for subcritical fluids of the one-dimensional analysis proposed by Kornhauser (1990) was chosen, and for the solution of the model computational programs were developed in the EES - Engineering Equation Solver software in which the calculation routines were constructed for iterative numerical solution in order to determine the optimum operating point of the cycle. To prove the model and the results obtained by the programs, the analysis presented by Kornhauser (1990) and the results compared were repeated. The results generated by the programs showed good results, being thus considered reliable in the application to predict performance of ejector cycles in operation with sub-critical fluids. The simulation system installed in the Laboratory of Thermal and Dynamic Fluid Studies of Unisinos (LETEF), built by Souza (2011) and later used by Noetzold (2016) in the simulation of the standard refrigeration cycle of an automotive air conditioning system, was changed for installation of the ejector in operation under COS cycle configuration. The choice of the COS cycle was due to the uncertainty of the oil return to compressor and the control of the separation of the phases of the refrigerant in the suction accumulator of the standard cycle. The system was subjected to the operating conditions set forth in the standard SAE J2765 OCT2008 (2008) and operated with R-134a. The results were compared with those of standard cycle by Noetzold (2016), showing a mean increase of the cycle COP of 25% for the low rotation range and 46% for the high rotation range and also compared to Lawrence (2012).
Keywords: Ejetor; Ar condicionado automotivo; Condenser outlet split; Ejector; Automotive air conditioning; Condenser outlet split; ACCNPQ::Engenharias::Engenharia Mecânica